Contextualizing the manifestation of gendered colonialist microaggressions: a qualitative study on post-colonial migration experiences among immigrant women - Piccinelli, Elena (2024)
Over the last decade, the framework of microaggressions has been adopted to examine subtle manifestations of discrimination from the perspective of socially disadvantaged groups. However, the microaggressions literature is strongly U.S.-centered, and very few studies have been conducted in other societal contexts, such as European countries characterized by distinct migration patterns and post-colonial intergroup relations. Moreover, foreign-born immigrant women have been overlooked in microaggression research. The present qualitative study draws upon post-colonial feminist theory and adopts an intracategorical intersectional approach to examine the experiences of foreign-born immigrant women in Portugal. Ten focus groups were conducted with 52 participants (Mage=34.2, SD = 10.2). Data were analyzed via a two-step process thematic analysis (TA) approach. First, codebook TA was used to produce nine themes building on previous microaggressions taxonomies. Then, reflexive TA was applied to generate four macro-themes related to post-colonial discourses. As a result, we propose a taxonomy of Gendered Colonialist Microaggressions and a theoretical framework linking these subtle forms of discrimination to social representations of immigrant women, rooted in colonial legacies and systemic power disparities. This study highlights the understudied psychological and societal implications of microaggressions in post-colonial settings, raising new questions and providing directions for future action.